The Impact of Insulin Degludec on Glucocorticoid-Induced Hyperglycemia in Patients with Diabetes and COVID-19 Infection - Varun Prasanna; Ravindranath Venketesan (Journal of Diabetology)
Abstract Objective: The objective was to assess the effectiveness and safety of insulin degludec (IDeg) on glycemic control in people with diabetes (PWD) hospitalized for moderate-to-severe coronavirus disease 2019 (COVID-19). Design: This study is a retrospective cohort study. Setting and Participants: Data were retrieved from medical records of PWD hospitalized for moderate-to-severe COVID-19. All patients who had steroid-induced hyperglycemia (SIH) were initiated with basal-bolus regimen with IDeg and human actaprid (HA) as part of their standard of care during admission. Data records at admission and discharge were retrieved and analyzed for hyperglycemia, insulin status, hypoglycemia, and other adverse events. The sigma plot version 15.0 was used to perform the statistical analysis and a P value (<0.05) was considered statistically significant. Results: The study retrieved data from medical records of 48 PWD hospitalized for moderate-to-severe COVID-19 and SIH for an average of 6.8 ± 2.5 days. There was a statistically significant decrease in average fasting plasma glucose from baseline (231.2 ± 91.1 mg/dL) to day 7/discharge (150.7 ± 32.1 mg/dL) (P < 0.05). The postprandial glucose showed a nonsignificant decrease; corresponding values were 295.0 ± 118.4 and 223.7 ± 65.4 mg/dL, respectively. The average IDeg dose increased significantly from baseline to day 7/discharge (15.6 ± 5.0 and 20.1 ± 6.5 units, respectively; P < 0.05). There was nonsignificant increase in average HA dose from 53.1 ± 16.7 IU on day 1 to 59.8 ± 16.6 IU on discharge day. No adverse events were reported in the medical records during hospitalization. Conclusion: IDeg is an effective and safe insulin for managing hyperglycemia in PWD who developed SIH during hospitalization for moderate-to-severe COVID-19.